2015
DOI: 10.1007/5584_2015_152
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Air Pollution Effects on the Respiratory System Based on Pulmonary Function Tests Performed During Spirometry Days

Abstract: The Polish Spirometry Day is an initiative aimed at increasing awareness of the causes, symptoms, course, and effects that accompany respiratory diseases, especially asthma and chronic obstructive pulmonary disease (COPD). In 2013, the second edition of the Spirometry Day was held. It gathered 180 medical centers and other institution. The final analysis encompassed a total of 1187 persons from 26 different locations, including rural areas, and smaller and larger city agglomerations. Of this total, 755 persons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Interestingly, experimental studies have demonstrated that the severity of viral respiratory infection in animal and in vitro models can be enhanced by exposure to air pollutants [ 42 , 43 , 44 ]. Furthermore, evidence suggests that air pollution is associated with lower lung function and decreased lung growth [ 45 ]. Several epidemiological studies have documented a positive association between exposure to particulate air pollution and respiratory symptoms, i.e., cough and wheeze, especially among children [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, experimental studies have demonstrated that the severity of viral respiratory infection in animal and in vitro models can be enhanced by exposure to air pollutants [ 42 , 43 , 44 ]. Furthermore, evidence suggests that air pollution is associated with lower lung function and decreased lung growth [ 45 ]. Several epidemiological studies have documented a positive association between exposure to particulate air pollution and respiratory symptoms, i.e., cough and wheeze, especially among children [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A negative relationship between NO 2 , SO 2 , and PM 10 and several lung function parameters (FVC, FEV1) was observed [ 77 ]. Dąbrowiecki et al reported that among people living in cities and close to the main roads, an increased number of obstruction cases, lower FEV1 as well as decreased FEV1/FVC were observed [ 78 ].…”
Section: Adultsmentioning
confidence: 99%
“…Poland has a high number of COPD and asthma sufferers (estimated at approx. 6 million in total), 80% of whom have not been adequately diagnosed and therefore not offered proper medical attention [15,16].…”
Section: Social Background Of the Issue And Literature Reviewmentioning
confidence: 99%